Foreign Tourists' Preferences for Wellness Tourism Products in Ubud - Prilandini, Ni Kadek Putri; Susianti, Hartanti Woro; Negarayana, Ida Bagus Putra; Tirtawati, Ni Made (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Wellness tourism in Ubud has started to re-emerge since 2020 with increasingly diverse wellness tourism product characteristics in line with the demand for wellness tourism products in Ubud, such as yoga retreats, meditation retreats, spiritual retreats, detoxes, and spa resorts. To focus on the development of the Ubud tourism area, it is necessary to identify the tendency of tourists to purchase tourism products so that the management of the Ubud tourism area. This study aims to determine the preferences (tendencies) of tourists in purchasing wellness tourism products in Ubud. A quantitative approach was used in this study by analyzing descriptive statistics and the number of respondents used was 120 people. This study resulted in foreign tourists' preferences for mind mental activity/education products being volunteers (volunteering), for health nutrition/diet products being detoxes (detox), for body physical fitness/beauty care products being pilates classes (pilates classes), for relaxation rest/meditation products being traditional massage (traditional massage).